Wood coloring agent based on metal-ligand coordination and application thereof

Through metal-ligand coordination technology, the wood particles are colored using transition metal salts and organic polyacids, and the problems of formaldehyde emission, organic dye fading and poor coating durability in the prior art are solved, and colored artificial-free plates with a stable color and high mechanical strength are achieved.

CN119773017AActive Publication Date: 2025-04-08TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510275628.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-08
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

The existing wood coloring technology relies on synthetic resin adhesives in paint, resulting in the release of formaldehyde gas under ultraviolet irradiation, which poses environmental pollution and health risks; organic dyes are easy to degrade, and the colors gradually fade during long-term use; the structural coloring coating has poor durability and is prone to fade after wear.

Method used

The wood colorant based on metal-ligand coordination is used to achieve coloring of wood particles through the coordination of transition metal salts and organic polyacids, and the color regulation is achieved by adjusting the types and dosages of metal salts and organic polyacids in the coordination system.

Benefits of technology

The whole body coloring without aldehyde is achieved, avoiding the release of formaldehyde gas and the fading of organic dyes, the color is stable and adjustable, and the wood particles are bonded together to meet environmental protection requirements and improve mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119773017A_ABST
    Figure CN119773017A_ABST
Patent Text Reader

Abstract

The invention discloses a wood coloring agent based on metal-ligand coordination and application of the wood coloring agent. The wood coloring agent comprises transition metal salt and organic polybasic acid containing two or more carboxyl characteristic functional groups, the transition metal salt and the organic polybasic acid are prepared according to the molar ratio of 1: 4-4: 1, and the wood coloring agent with metal-ligand coordination is obtained. By changing the types and the dosage of the transition metal salt and the organic polybasic acid in the wood coloring agent, the color is regulated and controlled. The invention further provides a preparation method of the colored formaldehyde-free artificial board, in the preparation method, based on a metal-ligand coordination strategy, the wood coloring agent is added into the wood particles, the coloring process and the forming process are combined, and coloring of the wood particles and whole-body coloring of the artificial board are achieved; the prepared colorful formaldehyde-free artificial board can present various adjustable colors, has excellent color wear-resistant durability and mechanical strength, and is suitable for preparation of novel large-size colorful formaldehyde-free artificial boards.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wood coloring, and more specifically to a wood coloring agent based on metal-ligand coordination and application thereof. Background Art

[0002] For many years, wood has been widely used in many fields such as construction, household items and tools due to its sustainability, high mechanical strength and aesthetic properties. In the past few decades, plastics and alloys have gradually become the main materials for furniture, door and window frames and household tools, but wooden materials still occupy an important position due to their environmentally friendly raw materials and renewability, especially artificial boards made from pressed waste wood particles. However, the coloring process of various wooden boards is overly dependent on synthetic resin adhesives in paints, which release a large amount of formaldehyde gas under ultraviolet irradiation, bringing environmental pollution and health risks. In recent years, researchers have been committed to developing new methods for coloring wood materials. Among them, the organic dye penetration method achieves coloring by immersing wood in organic dyes, but due to the easy degradation of organic dyes, its color will gradually fade during long-term use. The structural coloring method achieves wood coloring by constructing gold and silver coatings or photonic crystal coatings on the surface of wood, but due to the small size of the colorable wood and the poor durability of the coating, the coating is destroyed after wear and tear, exposing the base color of the wood, which has certain limitations.

[0003] In addition to organic dyes, inorganic pigments such as cinnabar, malachite and lapis lazuli are often used to color daily necessities and artworks due to their richness and durability. For example, they have been used in ancient ceramic glazes, traditional murals, and glass colorants. In recent years, researchers have used metal-ligand coordination to construct colored erasable paper, colored hydrogels, etc. Their colors come from the electronic transitions of metal ions and ligands. However, these studies basically stay at the stage of using metal-ligand coordination as ink coloring or using a single coordination system to color a single material field. No related research on the environmentally friendly coloring of wood with inorganic pigments has been reported. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the first object of the present invention is to provide a wood colorant based on metal-ligand coordination. The wood colorant provided by the present invention can use the metal-ligand coordination effect to color wood particles, and by changing the type and amount of transition metal salt and organic polyacid in the wood colorant, the color can be regulated.

[0005] The second object of the present invention is to provide a use of the wood stain as described above in preparing colored building materials.

[0006] The third object of the present invention is to provide a method for preparing a colored formaldehyde-free artificial board. The preparation method can realize full-body coloring of the artificial board. Compared with traditional coating or spray coloring, no harmful gas (such as formaldehyde) is released, and there is no fading problem of organic dyes. The full-body coloring effectively solves the wear and fading problem faced by methods such as structural color coating.

[0007] The fourth object of the present invention is to provide a colored formaldehyde-free artificial board. The colored formaldehyde-free artificial board prepared by the present invention can present a variety of adjustable colors, does not have the problem of harmful gas release and wear and fading, and the obtained artificial board also has excellent mechanical strength.

[0008] In order to achieve the above first object, the present invention adopts the following technical scheme: The present invention provides a wood stain based on metal-ligand coordination, the wood stain comprising a transition metal salt and an organic polyacid containing two or more carboxyl characteristic functional groups, wherein the transition metal salt and the organic polyacid are prepared in a molar ratio of 1:4-4:1 to obtain a wood stain with metal-ligand coordination. As an example, the molar ratio of the transition metal salt and the organic polyacid can be 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, etc.

[0009] Further, the transition metal salt includes but is not limited to one of iron salts, copper salts, cobalt salts, nickel salts, and zinc salts; as an example, the iron salt includes but is not limited to ferric chloride hexahydrate, ferric nitrate nonahydrate, ferric sulfate nonahydrate, ferric acetate and other ionic salts containing trivalent iron ions, and may also be ferrous chloride tetrahydrate, ferrous nitrate hexahydrate, ferrous sulfate heptahydrate and other ionic salts containing divalent iron ions, the copper salt includes but is not limited to copper sulfate pentahydrate, copper chloride dihydrate, copper nitrate trihydrate and other ionic salts containing divalent copper ions, the cobalt salt includes but is not limited to cobalt sulfate heptahydrate, cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt acetate tetrahydrate and other ionic salts containing divalent cobalt ions, the nickel salt includes but is not limited to nickel sulfate hexahydrate, nickel chloride hexahydrate, nickel nitrate hexahydrate, nickel acetate tetrahydrate and other ionic salts containing divalent nickel ions, the zinc salt includes but is not limited to zinc sulfate, zinc chloride monohydrate, zinc nitrate hexahydrate, zinc acetate dihydrate and other ionic salts containing divalent zinc ions; On the one hand, the organic polyacid coordinates with the transition metal salt to play a metal-ligand coordination role. By changing the type and amount of the transition metal salt and the organic polyacid, the coordination environment is adjusted to achieve color regulation. On the other hand, it plays a role similar to that of a binder to a certain extent, bonding the wood particles together, so that there is no need to add other binder components, meeting environmental protection requirements. As an example, in an embodiment of the present invention, the organic polyacid includes but is not limited to malic acid, succinic acid, malonic acid, oxalic acid, citric acid, tartaric acid and other organic polyacids containing two or more carboxyl characteristic functional groups.

[0010] In order to achieve the above second purpose, the present invention adopts the following technical solutions: The present invention provides a use of the wood colorant in preparing colored building materials.

[0011] In order to achieve the third object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a colored formaldehyde-free artificial board, comprising the following steps: Dissolving the wood stain as described above in water to obtain a staining solution; The pretreated wood particles are mixed with the coloring solution in proportion, and heated and dried under stirring or without stirring to complete the coloring; The colored wood particles are filled into a mold, hot-pressed, and demoulded to obtain the colored formaldehyde-free artificial board.

[0012] In the above preparation method, technicians can add some functional ingredients (excluding adhesives with bonding function) according to application needs to enhance the performance of the artificial board, but it will not affect the coloring performance of the wood colorant.

[0013] Furthermore, the pH value of the coloring solution generally affects the mechanical properties of the material. Studies have found that the pH value should be controlled within the range of 0-3 (excluding 0) or 11-13. In general, the pH value of the prepared coloring solution is between 0.5-3. At this time, no pH adjustment is required, that is, the pH value of the system after mixing the transition metal salt, organic polyacid and water is within the above-mentioned limited range. If the desired coloring solution is not strongly acidic, that is, the pH value is between 3-11 (excluding the end value), additional acid or alkali solution can be added for adjustment, such as hydrochloric acid, sulfuric acid, sodium hydroxide solution, etc.

[0014] Furthermore, the heating temperature is 40-85°C and the heating time is 24-48 h.

[0015] Furthermore, in the coloring solution, the concentration of the transition metal salt is 0.13-3.84 mol·L -1; For example, the concentration of the transition metal salt may be 0.13 mol·L -1 , 0.2mol·L -1 , 0.4 mol·L -1 , 0.6 mol·L -1 , 0.8 mol·L -1 , 1mol·L -1 , 1.2 mol·L -1 , 1.4 mol·L -1 , 1.6 mol·L -1 , 1.8 mol·L -1 , 2mol·L -1 , 2.2 mol·L -1 , 2.4 mol·L -1 , 2.6 mol·L -1 , 2.8 mol·L -1 , 3mol·L -1 、3.2mol·L -1 、3.4mol·L -1 、3.6mol·L -1 、3.8mol·L -1 wait; The mass ratio of the wood particles to the coloring solution is 1:1-1:5; illustratively, the mass ratio of the wood particles to the coloring solution can be 1:1, 1:2, 1:3, 1:4, 1:5, etc.

[0016] Furthermore, the wood particles are generally selected from wood chips, sawdust, wood shavings or various wood fibers such as bagasse particles with a size of 3-30 mm.

[0017] It should be noted that stirring is required during the coloring process of wood particles (i.e., the heating and drying process). Generally, due to the evaporation of water during the heating and drying process, the coloring area will have different shades. If stirring is introduced, the heated and dried materials will usually be dispersed more evenly and the coloring will be more even, so that the color of the final artificial board will be more uniform. On the contrary, if stirring is not introduced or the number of stirring times is too small, the artificial board may have a stronger sense of grain and a stronger sense of contrast between different areas. Therefore, the number of stirring times or time intervals can be adjusted according to actual needs, but it will not affect the obvious change in color. As an example, the material can be stirred every 1-4 hours during the heating and drying process.

[0018] The hot pressing process is the most critical factor affecting the mechanical strength of the artificial board. The hot pressing temperature is appropriate and the greater the pressure applied by the hot pressing, the greater the static bending strength of the artificial board. Since the present invention develops a colorful artificial board, the mechanical strength only needs to meet the application requirements. As an example, the hot pressing temperature is 60-210 ° C, the hot pressing time is 1-120 min, and the pressure is 3-100 MPa.

[0019] The material of the mold used in the present invention can be any metal or non-metal material with sufficient mechanical strength and sprayed with an anti-stick coating or covered with a film of a material such as polyimide on the surface. After the material preparation is completed, the mold needs to meet the detachable requirements so that the material can be completely removed.

[0020] Furthermore, the wood particles are pretreated as follows: After washing the wood particles, place them in an oven for heating and drying. After the dried wood particles are completely or partially decolorized, they are washed clean with a mixture of ethanol / water and heated and dried in an oven. For example, the heating temperature is 40-85°C and the heating time is 24-48 hours.

[0021] In order to achieve the fourth objective, the present invention adopts the following technical solutions: The present invention provides a colored formaldehyde-free artificial board prepared by the preparation method as described above.

[0022] The beneficial effects of the present invention are as follows: The invention discloses a wood colorant based on metal-ligand coordination. The wood colorant comprises a transition metal salt and an organic polyacid. The wood colorant is suitable for coloring wood particles, thereby preparing a colored formaldehyde-free artificial board.

[0023] The present invention also discloses a method for preparing a colored formaldehyde-free artificial board using the above-mentioned wood colorant. The method is essentially also a new formaldehyde-free coloring method for artificial boards. By adding the above-mentioned wood colorant to wood particles, formaldehyde-free full-body coloring can be achieved while completing the pressing and forming of the artificial board. By changing the type and amount of transition metal salts and organic polyacids in the wood colorant, the color is regulated, and the artificial board prepared by this coloring method presents a variety of adjustable colors. In addition, compared with the existing artificial board coloring method, no additional coating or spray coloring is required, and there is no release of harmful gases such as formaldehyde during long-term use, and there is no fading problem of organic dyes. At the same time, full-body coloring effectively solves the wear and fading problem faced by methods such as structural color coatings.

[0024] The colored formaldehyde-free artificial board prepared by the present invention is not only rich in color, but also has excellent mechanical strength. For example, the colored formaldehyde-free artificial board prepared by the present invention has a maximum static bending strength of 55.3 ± 3.1 MPa and an elastic modulus of 9.3 ± 1.9 GP, which is much higher than the strength requirement of 10 MPa for cement artificial boards in GB / T 24312-2009, and is almost equivalent to the bending strength of natural larch wood. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.

[0026] Figure 1 A schematic diagram of the process of coloring and molding the colored formaldehyde-free artificial board in the present invention is shown.

[0027] Figure 2 The actual picture of the colored formaldehyde-free artificial board prepared in Example 1 of the present invention and its visible light reflection spectrum scanned under an ultraviolet spectrophotometer are shown.

[0028] Figure 3 The actual picture of the colored formaldehyde-free artificial board prepared in Example 2 of the present invention and its visible light reflection spectrum scanned under an ultraviolet spectrophotometer are shown.

[0029] Figure 4 The actual picture of the colored formaldehyde-free artificial board prepared in Example 3 of the present invention and its visible light reflection spectrum scanned under an ultraviolet spectrophotometer are shown.

[0030] Figure 5 A physical picture of the large-sized colored formaldehyde-free artificial board prepared in Example 4 is shown.

[0031] Figure 6 The actual picture of the colored formaldehyde-free artificial board prepared in Example 5 and its visible light reflection spectrum scanned under an ultraviolet spectrophotometer are shown.

[0032] Figure 7 The actual pictures of the colored formaldehyde-free artificial boards obtained under different preparation conditions in the present invention are shown.

[0033] Figure 8 A comparison chart of the color wear durability test of the colored formaldehyde-free artificial board prepared in Example 5 and the commercial colored artificial board is shown.

[0034] Fig. 9 The figure shows the aging durability test of the wood stain prepared in Example 5. DETAILED DESCRIPTION

[0035] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0036] Example 1 This example is based on Figure 1 A process flow diagram is provided, which exemplarily provides a preparation process of a colored formaldehyde-free artificial board: (1) For commercially available sawdust particles, wash them with ethanol and deionized water, and dry them in an oven at 60 °C for 24 h; (2) The sawdust particles washed in step (1) are placed in a 6%-14% sodium hypochlorite solution, reacted in an ice-water bath for 2 h, washed with a mixed solution of water and ethanol in a volume ratio of 1:1, and heated and dried in an oven at 60 °C for 48 h. (3) Dissolve 1.46 g of cobalt sulfate heptahydrate (CoSO4·7H2O) and 1 g of anhydrous citric acid in 10 g of deionized water. 2+ ) and citric acid in a molar ratio of 1:1.

[0037] (4) Add 1 M NaOH solution to the solution obtained in step (3), and adjust the pH value to 3.0 using a pH meter to obtain a colored solution; (5) The sawdust particles obtained in step (2) and the coloring solution obtained in step (4) are mixed evenly, wherein the mass ratio of the sawdust particles to the coloring solution is 1:3, and then heated and dried in an oven at 60° C. for 48 h. During the drying process, the mixture is stirred every 3 h to maintain a uniform color, thereby completing the coloring of the sawdust particles.

[0038] (6) The colored sawdust particles obtained in step (5) are filled in a metal detachable mold covered with a polyimide film and hot-pressed, wherein the hot-pressing temperature is 120° C., the hot-pressing time is 5 min, and the pressure is 20 MPa.

[0039] (7) After the hot pressing is completed, the mold is disassembled and demolded.

[0040] Figure 2 The visible light reflectance spectrum (wavelength 390-780 nm) obtained by scanning the colored formaldehyde-free artificial board under the UV spectrophotometer is shown. Figure 2 The upper left corner is a real picture of a photo taken with a digital camera.

[0041] The static bending strength measured according to the American Society for Testing and Materials standard ASTM D1037-12 is 39.33 MPa.

[0042] Example 2 This example is based on Figure 1 A process flow diagram is provided, which exemplarily provides a preparation process of a colored formaldehyde-free artificial board: (1) For commercially available sawdust particles, wash them with ethanol and deionized water, and dry them in an oven at 60 °C for 30 h; (2) The sawdust particles washed in step (1) are placed in a 6%-14% sodium hypochlorite solution, reacted in an ice-water bath for 4 h, washed with a mixed solution of water and ethanol in a volume ratio of 1:1, and heated and dried in an oven at 60 °C for 48 h. (3) Dissolve 2.70 g of cobalt sulfate heptahydrate (CoSO4·7H2O) and 1 g of malonic acid in 10 g of deionized water. 2+ ) and malonic acid in a molar ratio of 1:1, and after mixing, no additional pH adjustment is required to obtain a colored solution.

[0043] (4) The sawdust particles obtained in step (2) and the coloring solution obtained in step (3) are mixed evenly, wherein the mass ratio of the sawdust particles to the coloring solution is 1:4, and then heated and dried in an oven at 60° C. for 36 h. During the drying process, the mixture is stirred every 2 h to maintain a uniform color, thereby completing the coloring of the sawdust particles.

[0044] (5) The colored sawdust particles obtained in step (4) are filled in a metal detachable mold covered with a polyimide film and hot pressed, wherein the hot pressing temperature is 130° C., the hot pressing time is 4 min, and the pressure is 15 MPa.

[0045] (6) After the hot pressing is completed, the mold is disassembled and demolded.

[0046] Figure 3 The visible light reflectance spectrum (wavelength 390-780 nm) obtained by scanning the colored formaldehyde-free artificial board under the UV spectrophotometer is shown. Figure 3 The upper left corner is a real picture of a photo taken with a digital camera.

[0047] The static bending strength measured according to the American Society for Testing and Materials standard ASTM D1037-12 is 30.43 MPa.

[0048] Example 3 This example is based on Figure 1 A process flow diagram is provided, which exemplarily provides a preparation process of a colored formaldehyde-free artificial board: (1) For commercially available sawdust particles, wash them with ethanol and deionized water, and dry them in an oven at 65 °C for 40 h; (2) The sawdust particles washed in step (1) are placed in a 6%-14% sodium hypochlorite solution, reacted in an ice-water bath for 3 h, washed with a mixed solution of water and ethanol in a volume ratio of 1:1, and heated and dried in an oven at 65°C for 40 h. (3) Dissolve 1.14 g of ferric chloride hexahydrate (FeCl3·6H2O) and 1 g of succinic acid in 10 g of deionized water. 3+ ) and succinic acid in a molar ratio of 1:2, and after mixing, no additional pH adjustment is required to obtain a colored solution.

[0049] (4) The sawdust particles obtained in step (2) and the coloring solution obtained in step (3) are mixed evenly, wherein the mass ratio of the sawdust particles to the coloring solution is 1:2, and then heated and dried in an oven at 60° C. for 36 h, stirring once every 1 h during the process to keep the color uniform.

[0050] (5) The colored sawdust particles obtained in step (4) are filled into a metal detachable mold covered with a polyimide film and hot pressed at a temperature of 110° C., a time of 3 min, and a pressure of 25 MPa.

[0051] (6) After the hot pressing is completed, the mold is disassembled and demolded.

[0052] Figure 4 The visible light reflectance spectrum (wavelength 390-780 nm) obtained by scanning the colored formaldehyde-free artificial board under the UV spectrophotometer is shown. Figure 4 The upper left corner is a real picture of a photo taken with a digital camera.

[0053] The static bending strength measured according to the American Society for Testing and Materials standard ASTM D1037-12 is 26.02 MPa.

[0054] Example 4 This example is based on Figure 1 A process flow diagram is provided, which exemplarily provides a preparation process of a colored formaldehyde-free artificial board: (1) For commercially available sawdust particles, wash them with ethanol and deionized water, and dry them in an oven at 65 °C for 30 h; (2) The sawdust particles washed in step (1) are placed in a 6%-14% sodium hypochlorite solution, reacted in an ice-water bath for 2 h, washed with a mixed solution of water and ethanol in a volume ratio of 1:1, and heated and dried in an oven at 65 °C for 30 h. (3) Dissolve 54.75 g of cobalt sulfate heptahydrate (CoSO4·7H2O) and 37.5 g of citric acid in 375 g of deionized water. 2+) and citric acid in a molar ratio of 1:1, and after mixing, no additional pH adjustment is required to obtain a colored solution.

[0055] (4) The sawdust particles obtained in step (2) and the coloring solution obtained in step (3) are mixed evenly, wherein the mass ratio of the sawdust particles to the coloring solution is 1:3, and then heated and dried in an oven at 60° C. for 24 h, stirring once every 2 h during the process to ensure uniform color.

[0056] (5) The colored sawdust particles obtained in step (4) are filled into a metal detachable mold covered with a polyimide film and hot pressed at a temperature of 120° C., a time of 10 min, and a pressure of 20 MPa.

[0057] (6) After the hot pressing is completed, the mold is disassembled and demolded.

[0058] Figure 5 Physical picture of taking pictures for digital camera.

[0059] The static bending strength measured according to the American Society for Testing and Materials standard ASTM D1037-12 is 28.19 MPa.

[0060] Example 5 This example is based on Figure 1 A process flow diagram is provided, which exemplarily provides a preparation process of a colored formaldehyde-free artificial board: (1) For commercially available sawdust particles, wash them with ethanol and deionized water, and dry them in an oven at 60 °C for 24 h; (2) The sawdust particles washed in step (1) are placed in a 6%-14% sodium hypochlorite solution, reacted in an ice-water bath for 2 h, washed with a mixed solution of water and ethanol in a volume ratio of 1:1, and heated and dried in an oven at 60 °C for 24 h. (3) Dissolve 1.46 g of cobalt sulfate hexahydrate (CoSO4·6H2O) and 1 g of citric acid in 10 g of deionized water. 2+ ) and citric acid in a molar ratio of 1:1, and after mixing, no additional pH adjustment is required to obtain a colored solution.

[0061] (4) The sawdust particles obtained in step (2) and the coloring solution obtained in step (3) are mixed evenly, wherein the mass ratio of the sawdust particles to the coloring solution is 1:3, and then heated and dried in an oven at 60° C. for 36 h, stirring once every 1 h during the process to ensure uniform color.

[0062] (5) The colored sawdust particles obtained in step (4) are filled into a metal detachable mold covered with a polyimide film and hot pressed at a temperature of 120° C., a time of 5 min, and a pressure of 20 MPa.

[0063] (6) After the hot pressing is completed, the mold is disassembled and demolded.

[0064] Figure 6 The visible light reflectance spectrum (wavelength 390-780 nm) obtained by scanning the colored formaldehyde-free artificial board under the UV spectrophotometer is shown. Figure 6 The upper left corner is a real picture of a photo taken with a digital camera.

[0065] The static bending strength measured according to the American Society for Testing and Materials standard ASTM D1037-12 is 33.18 MPa.

[0066] In order to demonstrate that the present invention can prepare artificial boards with various adjustable colors, the following sample boards were prepared.

[0067] (1) For commercially available sawdust particles, wash them with ethanol and deionized water, and dry them in an oven at 60 °C for 30 h; (2) The sawdust particles washed in step (1) are placed in a 6%-14% sodium hypochlorite solution, reacted in an ice-water bath for 2 h, washed with a mixed solution of water and ethanol in a volume ratio of 1:1, and heated and dried in an oven at 65 °C for 30 h. (3) A certain amount of metal ion salt and 1 g of organic polyacid are dissolved in 10 g of deionized water, wherein the molar ratio of metal ion to organic polyacid is between 1:4 and 2:1. After mixing, no additional pH adjustment is required or the pH value is adjusted to a specified value using 1 M NaOH solution to obtain a colored solution.

[0068] (4) The sawdust particles obtained in step (2) and the coloring solution obtained in step (3) are mixed evenly, wherein the mass ratio of the sawdust particles to the coloring solution is 1:3, and then heated and dried in an oven at 60° C. for 24 h, stirring once every 1 h during the process to ensure uniform color.

[0069] (5) The colored sawdust particles obtained in step (4) are filled into a metal detachable mold covered with a polyimide film and hot pressed at a temperature of 120° C., a time of 5 min, and a pressure of 20 MPa.

[0070] (6) After the hot pressing is completed, the mold is disassembled and demolded.

[0071] The coloring solution is prepared according to Table 1. The actual pictures of the colored formaldehyde-free artificial boards obtained under different preparation conditions are shown in Table 1. Figure 7 .

[0072] Table 1

[0073] Note: The molar ratio in Table 1 refers to the molar ratio of the transition metal salt to the organic polyacid; the pH in Table 1 refers to the pH value of the coloring solution; the transition metal salt concentration in Table 1 refers to the concentration of the transition metal salt in the coloring solution; the numbers in Table 1 refer to Figure 7 The winning bid is consistent.

[0074] Studies have shown that by adjusting the type and amount of transition metal salts and organic polyacids in the wood stain, as well as the pH value of the coloring solution and the concentration of transition metal salts, the following can be obtained: Figure 7 The colorful artificial board shown in the figure, where the type and amount of transition metal salt and organic polyacid are fixed, adjusting the pH value of the coloring solution and the concentration of transition metal salt will only affect the color depth of the artificial board, and will not cause such a large color span as from red to blue, or from green to red. Of course, Figure 7 The artificial board samples are provided only as examples. Under this wood stain system, hundreds of color changes can actually be presented, which are not listed here one by one.

[0075] Example 6 This example is based on Figure 1 A process flow diagram is provided, which exemplarily provides a preparation process of a colored formaldehyde-free artificial board: (1) For commercially available sawdust particles, wash them with ethanol and deionized water, and dry them in an oven at 60 °C for 30 h; (2) The sawdust particles washed in step (1) are placed in a 6%-14% sodium hypochlorite solution, reacted in an ice-water bath for 2 h, washed with a mixed solution of water and ethanol in a volume ratio of 1:1, and heated and dried in an oven at 60 °C for 30 h. (3) Dissolve 2.92 g of cobalt sulfate hexahydrate (CoSO4·6H2O) and 2 g of citric acid in 20 g of deionized water. 2+ ) and citric acid in a molar ratio of 1:1, and after mixing, no additional pH adjustment is required to obtain a colored solution.

[0076] (4) The sawdust particles obtained in step (2) and the coloring solution obtained in step (3) are mixed evenly, wherein the mass ratio of the sawdust particles to the coloring solution is 1:3, and then heated and dried in an oven at 60° C. for 30 h, stirring once every 1 h during the process to keep the color uniform.

[0077] (5) The colored sawdust particles obtained in step (4) are filled into a metal detachable mold covered with a polyimide film and hot pressed at a temperature of 150° C., a time of 5 min, and a pressure of 50 MPa.

[0078] (6) After the hot pressing is completed, the mold is disassembled and demolded.

[0079] The static bending strength measured according to the American Society for Testing and Materials standard ASTM D1037-12 is 49.49 MPa.

[0080] Color wear durability test The sample prepared in Example 5 and commercially available colored particleboard were strictly tested using a friction and color resistance test method that simulates the actual use environment. The results are shown in Figure 8 . By comparing the worn areas, it was found that after being subjected to a 60-second abrasion by a 100-grit grinding wheel, the commercially available particleboards with surface dye coating or colored PVC coating all showed obvious wear and fading, and even exposed the wood base color, with poor durability. However, the colored samples treated by the metal-ligand coordination in the present invention showed excellent color stability, which can be attributed to the fact that the present invention is a full-body coloring of the artificial board, so the above-mentioned wear and fading phenomenon does not exist. Through comparative analysis with existing products, the coloring technology of the present invention achieves effective improvement in surface coloring color stability and durability.

[0081] Colorant Aging Durability Test Considering that the pretreated wood particles themselves will also age, an aging test method simulating the actual use environment was used to conduct a strict test on the coloring solution prepared in Example 5 after drying the water (i.e., the wood colorant) to study the aging resistance of the wood colorant. The results are shown in Fig. 9 Comparing the reflectance spectra in the visible light region, it is found that at 60°C, the −2 After irradiation with 340 nm ultraviolet light for 0h, 200h, 400h, 600h, 800h, and 1000h (equivalent to 0-1 year of natural sunlight in Florida), the UV spectrum of the wood stain showed no obvious mutation, only a small degree of change in depth that was invisible to the naked eye.

[0082] In summary, through comparative analysis with existing products, the colorant of the present invention achieves effective improvement in color wear durability and long-term durability.

[0083] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A wood stain, characterized in that The wood colorant comprises a transition metal salt and an organic polyacid containing two or more carboxyl characteristic functional groups, wherein the transition metal salt and the organic polyacid are prepared in a molar ratio of 1:4-4:1 to obtain a wood colorant with metal-ligand coordination.

2. The wood stain according to claim 1, characterized in that The transition metal salt is selected from the group consisting of ferric chloride hexahydrate, ferric nitrate nonahydrate, ferric sulfate nonahydrate, ferric acetate, ferrous chloride tetrahydrate, ferrous nitrate hexahydrate, ferrous sulfate heptahydrate, cupric sulfate pentahydrate, cupric chloride dihydrate, cupric nitrate trihydrate, cobalt sulfate heptahydrate, cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt acetate tetrahydrate, nickel sulfate hexahydrate, nickel chloride hexahydrate, nickel nitrate hexahydrate, nickel acetate tetrahydrate, zinc sulfate, zinc chloride monohydrate, zinc nitrate hexahydrate, and zinc acetate dihydrate; The organic polyacid is selected from one of malic acid, succinic acid, malonic acid, oxalic acid, citric acid and tartaric acid.

3. Use of the wood colorant as claimed in claim 1 or 2 in the preparation of colored building materials.

4. A method for preparing a colored formaldehyde-free artificial board, characterized in that: The steps include: Dissolving the wood stain according to claim 1 or 2 in water to obtain a coloring solution; The pretreated wood particles are mixed with the coloring solution in proportion, and heated and dried under stirring or without stirring to complete the coloring; The colored wood particles are filled into a mold, hot-pressed, and demoulded to obtain the colored formaldehyde-free artificial board.

5. The preparation method according to claim 4, characterized in that: The pH value of the coloring solution is 1-3 or 11-13.

6. The preparation method according to claim 4, characterized in that: The heating temperature is 40-85 ℃ and the heating time is 24-48 h.

7. The preparation method according to claim 4, characterized in that: In the coloring solution, the concentration of the transition metal salt is 0.13-2.08 mol·L -1 ; The mass ratio of the wood particles to the coloring solution is 1:1-1:

5.

8. The preparation method according to claim 4, characterized in that: The hot pressing temperature is 60-210°C, the hot pressing time is 1-120 min, and the pressure is 3-100 MPa.

9. The preparation method according to claim 4, characterized in that: Wood pellets are pretreated as follows: The wood particles are washed and placed in an oven for heating and drying. After the dried wood particles are completely or partially decolorized, they are washed clean with a mixture of ethanol / water and heated and dried in an oven.

10. Colored formaldehyde-free artificial board, characterized in that: The method is described in any one of claims 4 to 9.

Citation Information

Patent Citations

  • Method for dyeing woods by using natural plant

    CN102785276A

  • Preparation method of colored wood-plastic material

    CN102837345A

  • Modified wood dyeing method

    CN104210004A

  • Method for inducing color changing of wood by grafting metal ions

    CN106584624A

  • Process for coloring wood with iron salt in water

    US4752297A